Poetic Approach In The Study Of A Drama Script: Analyzing The Disappointments Faced By Willy Loman In Arthur Miller's Death Of A Salesman In Teaching English As A Foreign Language Context - Hapsari, Astri (English Education Department, Universitas Islam Indonesia, 2012)
This article describes and explains how literary competence for the teaching of literature in English as a foreign language (EFL) context can be achieved by taking Culler's (1997) poetics in the study of literature as a theoretical framework. The implementation of this approach is discussed by using one of the famous drama scripts in American literature: Death of Salesman written by Arthur Miller. Following Culler's poetics approach, the analysis focuses on one of the themes found in the drama script: the disappointments faced by Willy Loman (the main character) which make up most of the plot with a dramatic ending: Willy's decision to suicide. This article aims to encourage EFL teachers who use literature as the object of study to take Culler's side by using poetics as the starting point in a literature study in order to improve the learners' literary competence.Key words: literary competence, poetic approach, teaching literature in EFL context, the study of a drama script, Death of a Salesman